Quantifying value co-creation: examining the relationship between realised value facets and customer experience in a B2B context. (4th July 2019) - Zeeshan, Muhammad; Rashid, Yasir; Ayub, Umer; Waseem, Ansar
Value co-creation has become central and one of the most researched topics among marketing scholars worldwide. This study discusses the relationship between value realisation facets and customer experience that emerges from a value co-creation process. With assumptions of a positivist paradigm, this study is responding to the call for quantification of value co-creation concept by developing a multidimensional scale to measure value co-creation in the context of information and communication technology (ICT) industry. Multivariate data analysis techniques like exploratory factor analysis (EFA), Cronbach's alpha and multiple regressions were used to check the reliability and validity of scale and test the hypothesis. The study finds that experience value (EV) is significantly and positively influenced by monetary value (MV), relationship value (RV) and functional value (FV). Moreover, it was also found that customer is more inclined towards RV and FV than that of MV to evaluate EV.